Perceived risks and consumer online purchase / Ayuni Thaherah Ruslin and Nuralya Ashikin Md Nor - Ruslin, Ayuni Thaherah; Md Nor, Nuralya Ashikin (2017)
Nowadays, online shopping becomes popular, especially among the Generation Y and Millennial. Malaysia has been forecast has a bright future for in online shopping. Consumer more intend to purchase online because they feel convenient and has 24 hours to do the purchase with using varies types of devises. The objective of this study is to identify the type’s perceived risk in consumer online purchase and to determine the most prominent type’s perceived risk toward consumer online purchase. Even thought, the online shopping currently increasing, there still has a cynical issues that will make a consumer worries to purchase. Perceived risk is the factor that influencing consumer when to purchase online. The anxiety feeling will keep the consumer away from the online shopping patterns. This study will help consumer or other parties find a ways or solution to avoid perceived risks in online shopping. Research design of this study was argumentative study which used secondary data such as journal article, websites, and online newspaper. This study focus on ten elements of perceived risk; financial risk, time risk, performance risk, psychological risk, physical risk, delivery risk, social risk, privacy risk, product risk and security risk. These studies show that previous researcher agreed that performance risk is the most risks that consumer concern. The performance of product or service was important to consumer when they purchase the items. Then this study suggests future research should investigate on consumer experience and handling the perceived risk in online purchase.